Bronchoscopic local steroid spray to prevent bronchial tuberculosis-induced cicatricial bronchial stenosis: A case series. Issue 28 (July 2018) - Yaguchi, Daizo; Ichikawa, Motoshi; Shizu, Masato; Inoue, Noriko; Kobayashi, Daisuke; Imai, Naoyuki
Abstract: Ratonale: Cicatricial bronchial stenosis or obstruction occurring in the healing process of endobronchial tuberculosis (ET) is a problematic complication of tuberculous airway lesions. Prevention by internal medical treatment is desired. Patient concerns: This case series describes four patients who diagnosed ET with Type IIIb (protruding ulcer-type) based on Arai's classification of bronchoscopic findings of bronchial tuberculosis. Diagnoses: Endobronchial tuberculosis. Interventions: A local steroid spray was applied bronchoscopically to active protruding ulcer-type lesions (which are likely to cause cicatricial stenosis) that extended in the transverse direction and occupied one-half or more of the circumference on bronchoscopy. Outcomes: Cicatricial stenosis was prevented in two of four patients. Treatment was discontinued in athird patient because tolerance could not be achieved, although the patient's condition had improved. In the fourth patient, treatment was switched to systemic steroid administration because of a problem with tolerance and the broad range of the lesion; however, stenosis remained. Lessons: Local steroid spray-applied bronchoscopically to bronchial tuberculosis lesions in the ulcer formation and granulation periods may help prevent stenosis.